HLA-A and -B alleles and haplotypes in 240 index patients with common variable immunodeficiency and selective IgG subclass deficiency in central Alabama - Barton James C; Bertoli Luigi F; Acton Ronald T (BMC, 2003)
Abstract Background We wanted to quantify HLA-A and -B phenotype and haplotype frequencies in Alabama index patients with common variable immunodeficiency (CVID) and selective IgG subclass deficiency (IgGSD), and in control subjects. Methods Phenotypes were detected using DNA-based typing (index cases) and microlymphocytotoxicity typing (controls). Results A and B phenotypes were determined in 240 index cases (114 CVID, 126 IgGSD) and 1,321 controls and haplotypes in 195 index cases and 751 controls. Phenotyping revealed that the "uncorrected" frequencies of A*24, B*14, B*15, B*35, B*40, B*49, and B*50 were significantly greater in index cases, and frequencies of B*35, B*58, B*62 were significantly lower in index cases. After Bonferroni corrections, the frequencies of phenotypes A*24, B*14, and B*40 were significantly greater in index cases, and the frequency of B*62 was significantly lower in index cases. The most common haplotypes in index cases were A*02-B*44 (frequency 0.1385), A*01-B*08 (frequency 0.1308), and A*03-B*07 (frequency 0.1000), and the frequency of each was significantly greater in index cases than in control subjects ("uncorrected" values of p < 0.0001, 0.0252, and 0.0011, respectively). After performing Bonferroni corrections, however, the frequency of A*02-B*44 alone was significantly increased in probands (p < 0.0085). Three other haplotypes were also significantly more frequent in index cases (A*03-B*14, A*31-B*40, and A*32-B*14). The combined frequencies of three latter haplotypes in index patients and control subjects were 0.0411 and 0.0126, respectively ("uncorrected" value of p < 0.0002; "corrected" value of p = 0.0166). Most phenotype and haplotype frequencies in CVID and IgGSD were similar. 26.7% of index patients were HLA-haploidentical with one or more other index patients. We diagnosed CVID or IgGSD in first-degree or other relatives of 26 of 195 index patients for whom HLA-A and -B haplotypes had been ascertained; A*01-B*08, A*02-B*44, and A*29-B*44 were most frequently associated with CVID or IgGSD in these families. We conservatively estimated the combined population frequency of CVID and IgGSD to be 0.0092 in adults, based on the occurrence of CVID and IgGSD in spouses of the index cases. Conclusions CVID and IgGSD in adults are significantly associated with several HLA haplotypes, many of which are also common in the Alabama Caucasian population. Immunoglobulin phenotype variability demonstrated in index cases and family studies herein suggests that there are multiple gene(s) on Ch6p or other chromosomes that modify immunoglobulin phenotypes of CVID and IgGSD. The estimated prevalence of CVID and IgGSD in central Alabama could be reasonably attributed to the fact that many HLA haplotypes significantly associated with these disorders are also common in the general population.